Punishments Connected with Person of Offender in Selected Countries of Ancient World - Michaela Uhlířová (Journal on European History of Law)
The article deals with sanctions directly connected with the person of offender in the established group of selected ancient states (Egypt, Mesopotamia, Hittite Empire). In this article these sanctions are divided and, furthermore, their impact from personal (humiliation), religious (posthumous life) as well as legal (“legal death”) view is discussed. In particular the legal norms extant in collections of laws (Mesopotamia, Hittite Empire) or court protocols (Egypt) were used as the basic sources for elaboration of this article.